HELPPPPPPPPPPPPPPPPPP PLEASEEEEEEEEE YOU ARE SAVING MY LIFE IF YOU HELP ME !!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!!

HELPPPPPPPPPPPPPPPPPP PLEASEEEEEEEEE YOU ARE SAVING MY LIFE IF YOU HELP ME class=
HELPPPPPPPPPPPPPPPPPP PLEASEEEEEEEEE YOU ARE SAVING MY LIFE IF YOU HELP ME class=
HELPPPPPPPPPPPPPPPPPP PLEASEEEEEEEEE YOU ARE SAVING MY LIFE IF YOU HELP ME class=

Respuesta :

Answer:

C. 8x - 16

D.  [tex]x^2[/tex] + 6x + 8

A. 2 (x + 3)

B. 7(2 - x)

C. -8x

D. 7x

Step-by-step explanation:

c.

To solve this problem, first, one must distribute, multiply every term inside the parenthesis by the term outside,

2(4x - 8)

=(2)(4x) + (2)(-8)

= 8x - 16

d.

To solve this problem, distribute, multiply every term inside one parenthesis by every term in the other, the combine like terms,

(x + 4)(x + 2)

= (x)(x) + (4)(x) + (2)(x) + (4)(2)

= [tex]x^2[/tex] + 4x + 2x + 8

= [tex]x^2[/tex] + 6x + 8

a.

Factor, write the given expression as the product of two expressions. Take out a common factor that both terms have,

2x + 6

= 2(x + 3)

b.

Factor this expression, take out a common factor, and rewrite the expression as the product of two other expressions,

14 - 7x

7(2 - x)

c.

Combine like terms,

2x - 10x

= -8x

d.

Combine like terms to solve this problem

3x + 4x

= 7x